Investigation of Somatic Mutations in Human Brains Targeting Genes Associated With Parkinson's Disease - Leija-Salazar, Melissa; Pittman, Alan; Mokretar, Katya; Morris, Huw; Schapira, Anthony H.; Proukakis, Christos (Frontiers in Neurology, 2020)
Background: Somatic mutations occur in neurons but their role in synucleinopathies is unknown. Aim: We aimed to identify disease-relevant low-level somatic single nucleotide variants (SNVs) in brains from sporadic patients with synucleinopathies and a monozygotic twin carrying LRRK2 G2019S, whose penetrance could be explained by somatic variation. Methods and Results: We included different brain regions from 26 Parkinsons disease (PD), 1 Incidental Lewy body, 3 multiple system atrophy cases and 12 controls. The whole SNCA locus and exons of other genes associated with PD and neurodegeneration were deeply sequenced using molecular barcodes to improve accuracy. We selected 21 variants at 0.33-5% allele frequencies for validation using accurate methods for somatic variant detection. Conclusions: We could not detect disease-relevant somatic SNVs, however we cannot exclude their presence at earlier stages of degeneration. Our results support that coding somatic SNVs in neurodegeneration are rare, but other types of somatic variants may hold pathological consequences in synucleinopathies.